Integrated early childhood development services improve mothers' experiences with prevention of mother to child transmission (PMTCT) programs in Malawi: a qualitative study - Kathryn Dovel; Pericles Kalande; Evelyn Udedi; Tijana Temelkovska; Julie Hubbard; Chipariro Mbalanga; Laurie Bruns; Siyenunu Mulungu; Sundeep Gupta; Linda Richter; Thomas J. Coates (BMC, 2021)
Abstract Background HIV-positive mothers who face the dual burden of HIV-positive status and motherhood, may benefit from holistic services that include early childhood development (ECD). We evaluated the acceptability and impact of integrated ECD-PMTCT interventions for mothers and their children. Methods We implemented an integrated ECD-PMTCT intervention in 4 health facilities in Malawi for HIV-positive mothers and their infants. WHO/UNICEF Care for Child Development (CCD) education and counseling sessions were offered during routine PMTCT visits between infant age 1.5-24 months. From June-July 2019, we conducted in-depth interviews with 29 mothers enrolled in the intervention for ≥6 months across 4 health facilities. The interview guide focused on perceived impact of the intervention on mothers' ECD and PMTCT practices, including barriers and facilitators, and unmet needs related to the program. Data were coded and analyzed using constant comparison methods in Atlas ti.8. Results The vast majority of mothers believed the ECD-PMTCT intervention improved their overall experience with the PMTCT services, strengthened their relationship with providers, and excited and motivated them to attend PMTCT services during the postpartum period. Unlike prior experience, mothers felt more welcome at the health facility, and looked forward to the next visit in order to interact with other mothers and learn new ECD skills. Mothers formed new social support networks with other mothers engaged in ECD sessions, and they provided emotional and financial support to one another, including encouragement regarding ART adherence. Mothers believed their infants reached developmental milestones faster compared to non-intervention children they observed at the same age, and they experienced improved engagement in caregiving activities among male caregivers. Nearly half of women requested additional support with depression or anxiety, coping mechanisms to deal with the stresses of life, or support in building positive dynamics with their male partner. Conclusion The integrated ECD-PMTCT intervention improved mother's experiences with PMTCT programs and health care providers, increased ECD practices such as responsive and stimulating parenting, and created social support networks for women with other PMTCT clients.